Gout Is Not Just Arthritis: Abnormal Cortical Thickness and Structural Covariance Networks in Gout - Yang, Yifan; Cheng, Yuqi; Wang, Xiangyu; Upreti, Bibhuti; Cui, Ruomei; Liu, Shuang; Shan, Baoci; Yu, Hongjun; Luo, Chunrong; Xu, Jian (Frontiers in Neurology, 2021)
Background： Hyperuricemia is the cause of gout. The antioxidant and neuroprotective effects of uric acid seem to benefit some patients with central nervous system injury. However, changes in the brain structure have not been discovered in patients with gout. Object： Clarify the changes in cortical thickness in patients with gout and the alteration of the structural covariant networks (SCN) based on cortical thickness. Methods: We collected structural MRIs of 23 male gout patients and 23 age-matched healthy controls. After calculating and comparing the difference in cortical thickness between the two groups, we constructed and analyzed the cortical thickness covariant networks of the two groups, and investigated for any changes in structural covariant networks (SCN) of gout patients. Results: Gout patients have thicker cortices in the left postcentral, left supramarginal, right medialtetemporal and right medialorbitofrontal regions and thinner cortices were found in the left insula, left superiorfrontal, right pericalcarine and right precentral regions. In SCN analysis, between-group differences in global network measures showed gout patients have a higher global efficiency. In regional network measures, more nodes in gout patients have increased centrality. In network hubs analysis, we found the transfer of the core hubs area, rather than the change in number, may be the characteristic of the gout’s cortical thickness covariant network. Conclusion: This is the first study on changes in brain cortical thickness and SCN based on graph theory in patients with gout. The present study found that, compared with healthy controls, gout patients show regional cortical thinning or thickening, and variation in the properties of the cortical thickness covariance network also changed. These alterations may be the combined effect of disease damage and physiological compensation. More research is needed to fully understand the complex underlying mechanisms of gout brain damage.